Semiotic Analysis of Gender Representation in Digital Crime Narratives in The Movie “ No More Bets” on Netflix - Vivi Fadhilah Safitri; Mukarto Siswoyo; Welly Wihayati (ann4publisher@gmail.com, 2026)
Background, Advances in digital technology have given rise to various forms of digital crime. One such crime is the case of cross-border online fraud in Asia, which has been made into a movie titled “No More Bets.”. Aim, This study was conducted to examine gender representation in films and the semiotic signs that shape gender meaning in narratives of digital crime. Methods, This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Data validity is tested through triangulation of methods. Results, The results of the study show that gender representation in films still reproduces gender power relations, as it continues to place women in a position that is unequal to men, with male characters being portrayed as dominant and female characters as vulnerable. Signs form gender meaning based on John Fiske's semiotics, at the level of reality, the level of representation, and the level of ideology. These three levels are interrelated in shaping the meaning of male and female roles in the digital crime system. This shows that gender meaning does not appear suddenly, but is constructed through visual signs, narratives, and ideologies present in films. Conclusions, Thus, the film “No More Bets” tends to reproduce the representation of men as the dominant party in the narrative of digital crime. Implication, This study confirms that a semiotic approach to examining gender representation on digital platforms is relevant and that gender sensitivity is necessary in the film industry to prevent the reproduction of gender stereotypes.